THE RESULTS OF BIOIMPEDANCE ANALYSIS OF CHILDREN OF PREPARATORY GROUPS OF PRESCHOOL EDUCATIONAL INSTITUTIONS WITH RISK OF HYPODYNAMIA - Перевощикова, Нина Константиновна; Селиверстов, Илья Александрович; Черных, Наталья Степановна; Дракина, Светлана Альбертовна (Mother and Baby in Kuzbass, 2024)
Increasing automation and information technologies in all spheres of human activity (education, work, leisure activities, etc.) has led to significant changes in the volume of motor activity - the growth of hypodynamia. The school variant of hypodynamia (as one of the variants of professional hypodynamia), which develops as a result of prolonged work without a significant change of position and the lack of systematic full-fledged physical activity during the period of being on the basis of an educational institution, deserves special attention [4]. The problem of hypodynamia is associated with most areas of activity and cannot keep specialists in pediatrics, hygiene of children and adolescents, pedagogy and economics aside, since it is children's health that occupies one of the leading roles in the long-term welfare of the state.In such circumstances of introduction of new technologies, intensification of the learning process and increasing hypodynamia, there is a need for modern methods of assessing the physical development of children. One of such methods is bioimpedance analysis (BIA), which quickly provides a wide range of data on the processes occurring in the child's organism.
Keywords: bioimpedance analysis; bioimpedanceometry; children; preschoolers; hypodynamia